State measures to encourage modernization of fuel and energy complex facilities - I. A. Guseva; C. K. Magomedov (Путеводитель предпринимателя, 2020)
The article is devoted to the problems of energy development in Russia, taking into account global trends, the trend of increasing the use of renewable energy sources, and increasing environmental requirements. In order to preserve the environment, the modern fuel and energy complex is included in the program of technological modernization, the main direction of which is the introduction of the best available technologies. The article discusses measures to encourage the modernization of fuel and energy facilities, as well as the main provisions of the Energy strategy of Russia